Crisis en la historia (UNIVERSIDAD DE SALMANCA, 1995)
CONTENIDO : REDERO SAN ROMAN, M.; WICKHAM, Ch.; FACI, J.; VACA LORENZO, A.; KAMEN, H.; ANATRA, B.; YUN CASALILLA, B.; MARCHENA FERNANDEZ, J.; GARAVAGLIA, J.C.; HERNANDEZ SANDOICA, E.; MARTINEZ QUINTEIROS, M.E.; ALCANTARA SAEZ, M.; DE VEGA, M.E.